2013
DOI: 10.1038/ncomms2460
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state proton transfer in the photoswitching reactions of the fluorescent protein Dronpa

Abstract: The reversible photoswitching between the 'on' and 'off' states of the fluorescent protein Dronpa involves photoisomerization as well as protein side-chain rearrangements, but the process of interconversion remains poorly characterized. Here we use time-resolved infrared measurements to monitor the sequence of these structural changes, but also of proton transfer events, which are crucial to the development of spectroscopic contrast. Light-induced deprotonation of the chromophore phenolic oxygen in the off sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
149
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(185 citation statements)
references
References 26 publications
32
149
4
Order By: Relevance
“…The 9 ps time constant, measured in 2 H 2 O at pD 7.8, was also in agreement with fluorescence measurements, which gave a 14 ps time constant in 1 H 2 O at pH 7.4 with excitation at 390nm and detection at 440 nm 9 . The IR difference spectrum of the primary photoproduct prominently lacks phenolate modes, thus excluding the possibility of excited state proton transfer, and was stable up to 100ps of the delays reported 10 . A recent study reported TR-IR measurements of the off state of the M159T mutant of Dronpa and came to very different conclusions 16 .…”
Section: As In the Aequorea Victoriamentioning
confidence: 87%
See 3 more Smart Citations
“…The 9 ps time constant, measured in 2 H 2 O at pD 7.8, was also in agreement with fluorescence measurements, which gave a 14 ps time constant in 1 H 2 O at pH 7.4 with excitation at 390nm and detection at 440 nm 9 . The IR difference spectrum of the primary photoproduct prominently lacks phenolate modes, thus excluding the possibility of excited state proton transfer, and was stable up to 100ps of the delays reported 10 . A recent study reported TR-IR measurements of the off state of the M159T mutant of Dronpa and came to very different conclusions 16 .…”
Section: As In the Aequorea Victoriamentioning
confidence: 87%
“…The fundamental mechanisms and sequence of events were investigated previously for the reversible photoswitching reactions of the wild type Dronpa fluorescent protein using visible-pump infrared-probe spectroscopy 10 . Previous proposals for the off-on switching invoked excited state proton transfer (ESPT) in addition to trans-cis photoisomerisation 9,11,12 .…”
Section: As In the Aequorea Victoriamentioning
confidence: 99%
See 2 more Smart Citations
“…Starting with a protonated chromophore in the trans isomeric state, the hypothesis of an excited state proton transfer (ESPT) being the driving force for back photoswitching competes with that of isomerization taking place in the protonated state of the chromophore, followed by deprotonation in the cis conformation as a ground state process. Several investigations by ultrafast infrared and UV-Vis spectroscopy on Dronpa suggest that the latter hypothesis is the correct one [40,41]. In IrisFP, transient femtosecond absorption spectroscopy suggested the existence, upon excitation of the trans protonated state, of two excited-state intermediates with lifetimes in the picosecond regime, which may represent twisted chromophore species, possibly leading to isomerization (Figure 6a).…”
Section: On-off Photoswitchingmentioning
confidence: 96%